What Process Algebra Proofs Use Instead of Invariance - Lamport, Leslie (1995)
Working on [110] got me thinking about how process-algebraic proofs work. This draft note describes my preliminary thoughts about what those proofs use instead of invariance. I never developed this far enough to know if it's right.